Leadership, Islamic Spirituality, and Javanese Mysticism: Cultural Analysis of Islamic Education of Panjang Jimat in Cirebon - Hermawan, Moh Hisyam; Sutisna, Deden; Yuliawati, Susi (Eduprof : Islamic Education Journal, 2025)
The Panjang Jimat Ritual in Cirebon is a tradition that blends Islamic spirituality and Javanese mysticism, passed down through generations within the Cirebon Palace. This research examines how the Panjang Jimat tradition reflects the fusion of Islamic values with local Javanese beliefs, seen in the use of heirloom objects as spiritual mediums and the role of the Sultan as the ritual leader. Additionally, this study explores the educational aspects of the ritual, where Islamic teachings are transmitted not only through formal education but also through cultural practices, shaping the spiritual and moral development of the community. Through a qualitative approach and literature analysis, this study shows that the Panjang Jimat not only serves as a religious ritual but also symbolizes social cohesion and cultural identity, strengthening the community’s connection with their ancestors and traditional values. Despite theological criticism regarding belief in the power of heirloom objects, the people of Cirebon view the ritual as a form of respect for their ancestors and a way to receive blessings from God. As times change, the Panjang Jimat tradition continues to adapt, addressing contemporary issues such as environmental sustainability and social inclusivity. This research demonstrates that Panjang Jimat is not just a tradition, but also a medium for dialogue between Islamic teachings, local wisdom, and Islamic education, maintaining its relevance amid modernization and social change